2019
DOI: 10.3389/fmicb.2019.00983
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Castanopsis carlesii Deadwood Mycobiome by Pacbio Sequencing of the Full-Length Fungal Nuclear Ribosomal Internal Transcribed Spacer (ITS)

Abstract: Short-read next generation sequencing (NGS) platforms can easily and quickly generate thousands to hundreds of thousands of sequences per sample. However, the limited length of these sequences can cause problems during fungal taxonomic identification. Here we validate the use of Pacbio sequencing, a long-read NGS method, for characterizing the fungal community (mycobiome) of Castanopsis carlesii deadwood. We report the successful use of Pacbio sequencing to generate long-read sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…These approaches are generally less laborious but require more efforts on molecular biology and bioinformatics. Culture-independent approaches have been rapidly developed over the past decade due to the applications of high-throughput sequencing technologies such as Next Generation Sequencing (NGS, e.g., 454 pyrosequencing, Illumina sequencing) and long-read Third Generation Sequencing (TGS, e.g., PacBio, Oxford Nanopore [ 38 , 39 , 40 ] Based on genetic and bioinformatic information obtained from culture-independent approaches, we can reasonably characterize the diversity and community composition as well as predict potential interactions and functions of microbes in various environments [ 41 , 42 , 43 ]. However, there are some pitfalls to culture-independent approaches, particularly relating to PCR biases [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are generally less laborious but require more efforts on molecular biology and bioinformatics. Culture-independent approaches have been rapidly developed over the past decade due to the applications of high-throughput sequencing technologies such as Next Generation Sequencing (NGS, e.g., 454 pyrosequencing, Illumina sequencing) and long-read Third Generation Sequencing (TGS, e.g., PacBio, Oxford Nanopore [ 38 , 39 , 40 ] Based on genetic and bioinformatic information obtained from culture-independent approaches, we can reasonably characterize the diversity and community composition as well as predict potential interactions and functions of microbes in various environments [ 41 , 42 , 43 ]. However, there are some pitfalls to culture-independent approaches, particularly relating to PCR biases [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, above some threshold, increasing sequencing depth is not expected to yield more recovered diversity (27). Purahong et al (21) showed also that sequencing depth alone is a poor performance metric to evaluate the representation of the fungal community. Kennedy et al (27) suggested a threshold of 100 reads per sample beyond which additional reads are unlikely to substantially shift community assessment of environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…PacBio has also been used for metabarcoding analysis of environmental fungal samples using the shorter ITS2 minibarcode and the large ribosomal subunit (28S), which are often used by short-read barcode studies ( Cline and Zak, 2015 ; Kyaschenko et al, 2017 ). Sequencing of the full length ITS1/2 DNA barcoding region by PacBio sequencers has been demonstrated on a wide variety of fungal species ( James et al, 2016 ; Walder et al, 2017 ; Heeger et al, 2018 ; Tedersoo et al, 2018 ; Purahong et al, 2019 ; Tedersoo and Anslan, 2019 ). A comparison between PacBio and nanopore sequencers found PacBio to be more efficient in the metabarcoding of complex environmental fungal samples due to errors found in nanopore sequencing ( Loit et al, 2019 ).…”
Section: Long-read Sequencing Applied To Infectious Disease Investigationsmentioning
confidence: 99%